POLYPLOIDY INDUCTION BY COLCHICINE TREATMENT IN GOLDEN BERRY (PHYSALIS PERUVIANA), AND EFFECTS OF POLYPLOIDY ON SOME TRAITS - N. Comlekcioglu; M. Ozden (Journal of Animal and Plant Sciences, 2019)
Goldenberry (Physalis peruviana L) an important small fruit that is growing rapidly around the globe. Different colchicine treatments (0.0, 0.3, 0.6, and 0.9% w/v) were used to induce tetraploidy in goldenberry plants. Three colchicine treatment methods were evaluated; i) immersion of seeds in colchicines solution, ii) immersion of germinated seeds (with roots about 2 mm long) in colchicine and iii) incubation of seeds on semi solid Murashige and Skoog (MS, 1962) medium containing colchicines. Experiments were set up with three factors factorial experimental design with three replicates, where the colchicine application method was the main factor of variation, the concentrations was the secondary factor and the exposure time was the third factor. Twenty seeds for each treatment, with three replications were used.  Diploid plants grown from untreated seeds were used as controls. The incubation of seeds on colchicine containing MS medium was found to be the only effective method and tetraploid plants were produced in this way. The highest tetraploidy was achieved by adding 0.06 and 0.09% colchicine to MS medium. An exposure time 21-30 d was sufficient to produce tetraploid plants. Ploidy determination was made by flow cytometry. The polyploidization rate ranged between 4.1-58.8%. Tetraploid plant could not be obtained from other treatments. Statistical analysis was not performed since data could not be obtained from the lowest groups.  The induced tetraploid plants were with larger plants, fruits, leaves, and stomata, higher chlorophyll content and lower stomata density compared to diploid control plants. The results have shown that colchicine should be added to the in vitro culture medium at least 0.6% and 0.9% doses and the seeds should be cultured for at least 30 days. An analysis of variance (two sample T-test) was performed at the 5% significance level to comparison of the morphologic characteristics of diploid and tetraploid plants.
Keywords: chromosome doubling; flow cytometry; colchicine; goldenberry; stomata